ASEAN ports and the liberalisation of the maritime trade sector - Zul Kepli, Mohd Yazid (Transstellar Journal Publications and Research Consultancy Private Limited (TJPRC), 2016)
With regional liberalisation of trade and services being top on ASEAN agenda, steps are being taken to further liberalize trade and services sectors. This article explores ASEAN maritime logistic industry and analyzes how the liberalisation of maritime trade, and now, ASEAN economic integration, impacts on the conduct, structure and performance of ASEAN ports. Malaysian is chosen as a case study. This paper also looks at the opportunities and challenges face by ASEAN ports especially from the aspect of international cooperation, efficiency, environmental issues and restrictions and barriers.